Rechargeable lithium battery

CN116230877BActive Publication Date: 2026-10-27SAMSUNG SDI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211515452.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-03
Filing Date
2022-11-29
Publication Date
2026-10-27
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

[0004]然而,当电池的内部温度达到预定值或更高值时,切断电流的温度传感/电流切断系统存在即使在约60℃或更低的一般高温下也运行的问题,因此当运行温度设定为较高时,电流切断系统通常运行较晚,在确保过充电安全方面受到限制

Benefits of technology

[0008]在根据实施方式的可再充电的锂电池中,在过充电期间当电池中产生大量的气体并且压力充分增加时,过充电安全装置快速地运行而切断电流,并且因此确保了过充电安全性。另外,在运行期间可实现卓越的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116230877B_ABST
    Figure CN116230877B_ABST
Patent Text Reader

Abstract

The present invention relates to a rechargeable lithium battery. The rechargeable lithium battery includes: a positive electrode including a positive active material, the positive active material including secondary particles in which a plurality of primary particles are aggregated, and a boron coating layer provided on a surface of the secondary particles and including a lithium borate, the secondary particles having at least a part of the primary particles radially arranged, the secondary particles including a lithium nickel-based composite oxide; a negative electrode; a separator between the positive electrode and the negative electrode; an electrolyte including vinylene carbonate; and a case containing the positive electrode, the negative electrode, the separator, and the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to rechargeable lithium batteries that ensure overcharge safety. Background Technology

[0002] Portable information devices (such as cell phones, laptops, smartphones, etc.) or electric vehicles already use rechargeable lithium batteries with high energy density and portability as their power source. Recently, research has been actively underway to use rechargeable lithium batteries with high energy density as a power source or energy storage source for hybrid or electric vehicles.

[0003] However, with the commercialization of rechargeable lithium batteries in various fields, overcharging problems have emerged, where these batteries are charged beyond their specified voltage values. During overcharging, the internal pressure and temperature of the rechargeable lithium battery can increase due to chemical reactions in the battery's internal materials, potentially leading to accidents such as thermal runaway. To prevent these accidents, the battery can be equipped with a system that cuts off the current when the internal pressure and temperature reach predetermined or higher values.

[0004] However, when the battery’s internal temperature reaches a predetermined value or higher, the temperature sensing / current cut-off system has a problem operating even at generally high temperatures of around 60°C or lower. Therefore, when the operating temperature is set high, the current cut-off system usually operates later, which limits its ability to ensure overcharge safety.

[0005] When the internal pressure of the battery reaches a predetermined value or higher, the temperature sensing / current cut-off system, which cuts off the current, suffers from a problem where the overcharge safety system fails to function properly because the internal pressure of the battery does not rise quickly enough even after overcharging. This can lead to accidents such as battery explosions after being left unattended. Accordingly, rechargeable lithium batteries equipped with safety devices that operate rapidly during overcharging to ensure safety. Summary of the Invention

[0006] Rechargeable lithium batteries ensure overcharge safety by quickly activating a safety device when overcharging beyond a specified voltage value.

[0007] In one embodiment, the rechargeable lithium battery includes: a positive electrode comprising a positive electrode active material comprising secondary particles and a boron coating comprising lithium borate disposed on the surface of the secondary particles, wherein a plurality of primary particles are aggregated in the secondary particles and the secondary particles have at least a portion of the primary particles arranged radially, the secondary particles comprising a lithium nickel composite oxide; a negative electrode; a separator between the positive electrode and the negative electrode; an electrolyte comprising vinylene carbonate; and a casing containing the positive electrode, the negative electrode, the separator, and the electrolyte.

[0008] In the rechargeable lithium battery according to the embodiment, when a large amount of gas is generated in the battery and the pressure increases sufficiently during overcharging, the overcharge safety device quickly operates to cut off the current, thus ensuring overcharge safety. Furthermore, excellent performance is achieved during operation. Attached Figure Description

[0009] Figure 1 A schematic diagram illustrating the shape of the plate-like primary particles.

[0010] Figure 2 This is a view used to explain the radial definition in secondary particles.

[0011] Figure 3 This is a schematic diagram illustrating the cross-sectional structure of the secondary particles according to an embodiment.

[0012] Figure 4 A cross-sectional view of a rechargeable lithium battery according to an embodiment is shown for illustrative purposes.

[0013] Figure 5 This is a scanning electron microscope (SEM) image of the cross-section of the positive electrode active material precursor prepared in Example 1.

[0014] Figure 6 This is a SEM image of the cross-section of the positive electrode active material prepared in Example 1.

[0015] Figure 7 This is a time-of-flight secondary ion mass spectrometry (ToF-SIMS) analysis image of the surface of the positive electrode active material prepared in Example 1.

[0016] Figure 8 for Figure 7 Mass spectrometry results from ToF-SIMS analysis.

[0017] Figure 9 This is a transmission electron microscope (TEM) image of primary particles exposed on the surface of secondary particles in the positive electrode active material prepared in Example 1.

[0018] Figure 10 for Figure 9 The image shows a TEM-EELS (Transmission Electron Microscopy-Electron Energy Loss Spectroscopy) analysis of a total of 10 points, from point 1 to point 10.

[0019] Figure 11 A graph showing the boron content of the boron coating (outer side) and the boron-coated portion at the grain boundaries (inner side) based on the amount of boron added, as measured by inductively coupled plasma (ICP) emission spectroscopy.

[0020] Figure 12A graph illustrating the assessment of the amount of gas generated in the battery cells during overcharging for Examples 1 and Comparative Examples 1 to 3.

[0021] Figure 13 The graph shows the current variation based on the charging voltage for evaluating individual battery cells in Example 2, Comparative Example 4, Reference Example A, and Reference Example B.

[0022] <Explanation of Figure Markers>

[0023] 11: Secondary particles 12: Internal part of secondary particles

[0024] 13: Primary particles 14: External portion of secondary particles

[0025] 100: Rechargeable lithium battery; 112: Negative electrode

[0026] 113: Diaphragm; 114: Positive electrode

[0027] 120: Housing; 140: Sealing component Detailed Implementation

[0028] Specific implementations will be described in detail below so that those skilled in the art can readily implement them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the exemplary implementations set forth herein.

[0029] The terminology used herein is for describing exemplary embodiments only and is not intended to limit this disclosure. Unless the context clearly indicates otherwise, singular expressions also include plural expressions.

[0030] As used herein, "any combination thereof" means mixtures of components, laminates, complexes, copolymers, alloys, blends, and reaction products, etc.

[0031] In this document, it should be understood that terms (such as “comprising,” “including,” or “having”) are intended to indicate the presence of a feature, quantity, step, element, or any combination thereof of the implementation, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or any combination thereof.

[0032] In the accompanying drawings, for clarity, the thicknesses of layers, films, panels, areas, etc., are enlarged, and throughout the specification, the same reference numerals denote the same elements. It will be understood that when an element (such as a layer, film, area, or substrate) is referred to as being "on" another element, it may be directly on the other element, or an intervening element may be present. In contrast, when an element is referred to as being "directly on" another element, no intervening element is present.

[0033] In addition, in this paper, “layer” includes not only the shape formed on the entire surface when viewed from a plan view, but also the shape formed on a portion of the surface.

[0034] Alternatively, the average particle size can be measured using methods well known to those skilled in the art, for example, by a particle size analyzer, or by transmission electron microscopy or scanning electron microscopy. Optionally, the average particle size can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and thereby calculating. Unless otherwise defined, the average particle size (D50) may mean the diameter of the particles that constitute 50% of the total volume in the particle size distribution.

[0035] In this article, "or" is not interpreted as exclusive; for example, "A or B" is interpreted as including A, B, A+B, etc.

[0036] In one embodiment, the rechargeable lithium battery includes: a positive electrode comprising a positive electrode active material, the positive electrode active material comprising secondary particles and a boron coating disposed on the surface of the secondary particles and comprising lithium borate, wherein a plurality of primary particles are aggregated in the secondary particles and the secondary particles have at least a portion of the primary particles arranged radially, the secondary particles comprising a lithium nickel composite oxide; a negative electrode; a separator between the positive electrode and the negative electrode; an electrolyte comprising vinylene carbonate; and a casing containing the positive electrode, the negative electrode, the separator and the electrolyte.

[0037] When this rechargeable lithium battery is charged with an abnormal voltage (e.g., in the range of approximately 4.5V to approximately 5.0V, such as approximately 4.7V or higher, or approximately 4.8V or higher) at the specified voltage or higher, a large amount of gas is generated inside the battery. This causes the overcharge safety device to quickly activate, cutting off the current and transferring heat to prevent accidents such as fires. Furthermore, below the specified voltage, since no additional gas is generated, the battery can resume normal operation and exhibit excellent performance, such as cycle life characteristics.

[0038] It has been reported that the use of electrolyte additives (such as vinylene carbonate) in the electrolyte improves the cycle life of the battery. However, these electrolyte additives can reduce the amount of gas generated during overcharging, and consequently, safety devices may not activate because the internal pressure of the battery does not rise at a sufficiently rapid rate, thus potentially leading to problems such as continued thermal runaway after overcharging.

[0039] Conversely, in this embodiment, because a specific positive electrode active material is simultaneously applied, when vinylene carbonate is added to the electrolyte, no gas is generated below a specified voltage. Instead, a large amount of gas is generated only when charging at a specified voltage or higher (e.g., about 4.5V to about 5.0V, or about 4.7V or higher, or about 5.0V or higher), allowing the safety device to operate quickly and successfully ensuring the overvoltage safety of the rechargeable lithium battery. On the other hand, when the rechargeable lithium battery is charged at an overvoltage of, for example, about 5.0V or higher, the amount of gas generated per unit weight of positive electrode active material in the battery can be about 3 cc / g or higher. The amount of gas generated can be measured using the method of Evaluation Example 4.

[0040] positive electrode

[0041] The positive electrode for a rechargeable lithium battery according to an embodiment may include a positive current collector and a layer of positive active material on the positive current collector. The positive active material layer may include a positive active material and may further include a binder and / or a conductive material.

[0042] Positive electrode active material

[0043] The positive electrode active material for a rechargeable lithium battery according to an embodiment includes secondary particles and a boron coating disposed on the surface of the secondary particles and including lithium borate, wherein a plurality of primary particles are aggregated in the secondary particles, and the secondary particles have at least a portion of the primary particles arranged radially, the secondary particles including lithium nickel composite oxide.

[0044] The boron coating can be applied to the surface of the secondary particles and can be uniformly coated on the surface of the secondary particles. The lithium borate of the boron coating can be represented as lithium boron oxide, and may include LiBO2, Li3B7O, etc. 12 Li6B4O9, Li3B 11 O 18 Li₂B₄O₇, Li₃BO₃, Li₈B₆O 13 Li5B3O7, Li4B2O5, Li 10 B4O 11 Li8B2O7 or any combination thereof.

[0045] Based on the total weight of the positive electrode active material, the content of lithium borate in the boron coating can be from about 0.02 wt% to about 0.5 wt%, for example, about 0.03 wt% to about 0.4 wt%, about 0.04 wt% to about 0.3 wt%, or about 0.05 wt% to about 0.2%. When this content range is met, the boron coating does not act as a resistor, improves the structural stability of the positive electrode active material, and improves cycle life characteristics. In addition, lithium borate in this content range has a synergistic effect with vinylene carbonate in the electrolyte to generate a large amount of gas during overcharge, thereby improving overcharge safety and exhibiting excellent performance during normal operation.

[0046] The positive electrode active material according to the embodiments may further include a boron-doped layer inside the primary particles exposed on the surface of the secondary particles.

[0047] Conventionally, when boron is coated onto positive electrode active materials, a common method is to heat-treat the lithium metal composite oxide by mixing it with boron raw material in a wet or dry manner after preparing the lithium metal composite oxide. However, in this case, boron acts as a resistor on the surface of the positive electrode active material, resulting in a significant deterioration in capacity and cycle life. On the other hand, according to an embodiment, when preparing a secondary particulate positive electrode active material in which at least a portion of the primary particles are radially arranged, a boron coating and a boron doping layer can be simultaneously formed in the positive electrode active material. This method involves adding lithium raw material and boron raw material together to a specific positive electrode active material precursor (such as nickel hydroxide), and then heat-treating the mixture under specific conditions. When the boron coating and boron doping layer are formed simultaneously in appropriate amounts, boron no longer acts as a resistor but improves the structural stability of the positive electrode active material, while also improving the capacity characteristics and high-temperature cycle life characteristics of the rechargeable lithium battery. In addition, during abnormal overcharging, the boron coating and boron doping layer can help generate a large amount of gas, thus rapidly activating safety devices and improving overcharge safety.

[0048] The boron-doped layer can be considered to be disposed inside the secondary particles; specifically, it can be considered to be disposed inside the primary particles exposed on the surface of the secondary particles. The primary particles exposed on the surface of the secondary particles can refer to the primary particles in the outermost portion of the secondary particles. For example, the boron-doped layer can be disposed at a depth of approximately 10 nm from the outer surface of the primary particles exposed on the surface of the secondary particles. If the outer surface of the primary particles exposed on the surface of the secondary particles is 0 nm, the boron-doped layer can be considered to exist at a depth of approximately 0 nm to approximately 10 nm from the surface. In other words, the boron-doped layer can exist at a depth of approximately 10 nm from the surface of the secondary particles. When the surface of the secondary particles is approximately 0 nm, the boron-doped layer can exist at a depth of approximately 0 nm to approximately 10 nm from the surface.

[0049] The boron-doped layer can exist, for example, at a depth of about 9 nm, about 8 nm, about 7 nm, about 6 nm, about 5 nm, about 4 nm, about 3 nm, or about 2.5 nm from the outer surface of the primary particle exposed to the surface of the secondary particle. This boron-doped layer may differ from the boron coating and also from the grain boundary boron coating portion described later, thus contributing to the structural stability of the positive electrode active material.

[0050] On the other hand, the positive electrode active material may further include a grain boundary boron coating portion, which is disposed on the surface of the primary particles inside the secondary particles and includes lithium borate. This grain boundary boron coating portion is not present on the surface of the secondary particles, but rather inside the secondary particles, and can be coated along the interface of the primary particles. In this document, "inside the secondary particles" means the entire interior except for the surface, for example, the entire interior from the outer surface to a depth of about 2 μm, or the portion that distilled water cannot reach when the secondary particles of the positive electrode active material are rinsed with distilled water.

[0051] According to the embodiments, the weight of the boron coating is greater than the weight of the intergranular boron coating portion. For example, the weight of the boron coating may be four times the weight of the intergranular boron coating portion. For example, based on the total amount of the boron coating and the intergranular boron coating portion, the amount of the included intergranular boron coating portion may be about 2 wt% to about 30 wt%, specifically about 3 wt% to about 25 wt% or about 5 wt% to about 20 wt%, and the amount of the included boron coating may be about 70 wt% to about 98 wt%, about 75 wt% to about 97 wt%, or about 80 wt% to about 95 wt%, etc. For example, the weight ratio of the boron coating and the intergranular boron coating portion may be about 70:30 to about 98:2, for example, about 75:25 to about 97:3 or about 80:20 to about 95:5. When the above content ratio includes boron coating and intergranular boron coating portions, boron does not act as a resistor, but rather improves the performance of the rechargeable lithium battery, while also improving the capacity characteristics and cycle life characteristics of the rechargeable lithium battery.

[0052] Based on the total weight of the positive electrode active material, the content of the boron coating (i.e., the content of lithium borate in the boron coating) can be, for example, about 0.02 wt% to about 0.5 wt%, about 0.03 wt% to about 0.4 wt%, about 0.04 wt% to about 0.3 wt%, or about 0.05 wt% to about 0.2 wt%. Based on the total weight of the positive electrode active material, the content of the intergranular boron coating portion (i.e., the content of lithium borate in the intergranular boron coating portion) can be, for example, about 0.001 wt% to about 0.05 wt%, about 0.001 wt% to about 0.04 wt%, about 0.002 wt% to about 0.03 wt%, or about 0.003 wt% to about 0.02 wt%, but is not limited thereto. When the content of the boron coating used for the positive electrode active material and the content of the intergranular boron coating portion are within the above ranges, both the capacity characteristics and cycle life characteristics of the rechargeable lithium battery can be improved.

[0053] Based on the total amount of positive electrode active material, the total amount of boron coating and intergranular boron coating portion can be approximately 0.1 mol% to approximately 5 mol%, for example, approximately 0.1 mol% to approximately 3 mol%, approximately 0.1 mol% to approximately 2.5 mol%, approximately 0.1 mol% to approximately 2 mol%, approximately 0.1 mol% to approximately 1.5 mol%, or approximately 0.5 mol% to approximately 1.3 mol%. If the total amount of boron coating and intergranular boron coating portion exceeds the above range, the initial discharge capacity can be reduced, and the cycle life characteristics can be degraded. In particular, if the amount of boron coating present on the surface of secondary particles is excessive, boron acts as a resistor, and the initial discharge capacity of the rechargeable lithium battery can be significantly reduced.

[0054] On the other hand, the positive electrode active material includes secondary particles, in which at least two primary particles are aggregated, and at least a portion of the primary particles have a radially arranged structure. At least some of the primary particles may be plate-like. Plate-like primary particles may have a thickness smaller than the length of their major axis. Here, the length of the major axis refers to the maximum length with respect to the widest surface of the primary particle. That is, the primary particles may have a structure in which the length (t) in one axial direction (i.e., the thickness direction) is smaller than the length (a) of the major axis in another direction (i.e., the planar direction).

[0055] Figure 1 This is a schematic diagram illustrating the plate-like structure of the primary particles of the first positive electrode active material. (Reference) Figure 1 The primary particles according to the embodiments have various detailed shapes while possessing basic plate structures, such as (A) polygonal (e.g., hexagonal) nanoplates, (B) nanodiscs, and (C) cuboids. Figure 1In this context, "a" refers to the length of the major axis of the primary particle, "b" refers to the length of the minor axis of the primary particle, and "t" refers to the thickness of the primary particle. The thickness t of the primary particle can be less than the length of the major axis a and the length of the minor axis b in the planar direction. In the planar direction, the length of the major axis a can be longer than or equal to the length of the minor axis b. The direction defining the thickness t in the primary particle is defined as the thickness direction, and the direction having lengths a and b is defined as the planar direction.

[0056] In the positive electrode active material, at least some of the primary particles may have a radially arranged structure, for example, the long axis of the primary particles may be arranged in the radial direction. Figure 2 This is a view used to explain the radially defined arrangement of secondary particles according to an embodiment. In the embodiment, a radially arranged structure means as follows: Figure 2 The thickness t of the primary particle shown is perpendicular to the direction R from the center of the secondary particle to the surface, or within an angle of approximately ±5° perpendicular to the direction R from the center of the secondary particle to the surface.

[0057] The average length of the primary particles in the secondary particles can be approximately 0.01 μm to approximately 5 μm, for example, approximately 0.01 μm to approximately 2 μm, approximately 0.01 μm to approximately 1 μm, approximately 0.02 μm to approximately 1 μm, approximately 0.05 μm to approximately 0.5 μm, or approximately 150 nm to approximately 500 nm. Here, when the primary particles are plate-shaped, "average length" refers to the average length 'a' of the major axis in the planar direction; when the primary particles are spherical, "average length" refers to the average particle size.

[0058] When the primary particles are plate-shaped, the average thickness of the primary particles may be, for example, greater than or equal to about 50 nm, greater than or equal to about 100 nm, greater than or equal to about 200 nm, greater than or equal to about 300 nm, greater than or equal to about 400 nm, greater than or equal to about 500 nm, greater than or equal to about 600 nm, greater than or equal to about 700 nm, greater than or equal to about 800 nm, or greater than or equal to about 900 nm, and for example, less than or equal to about 5 μm, less than or equal to about 4 μm, less than or equal to about 3 μm, less than or equal to about 2 μm, less than or equal to about 1 μm, less than or equal to about 900 nm, less than or equal to about 800 nm, less than or equal to about 700 nm, less than or equal to about 600 nm, less than or equal to about 500 nm, or less than or equal to about 200 nm, for example, about 100 nm to about 200 nm. In addition, in the primary particles, the ratio of average thickness to average length can be about 1:1 to about 1:10, for example about 1:1 to about 1:8, about 1:1 to about 1:6 or about 1:2 to about 1:5.

[0059] As mentioned above, when the average length, average thickness, and ratio of average thickness to average length of the primary particles meet the above ranges, and at least a portion of the primary particles are radially arranged, there may be relatively more lithium diffusion paths between the grain boundaries on the surface side, and a large number of crystal faces capable of lithium transfer are exposed on the outside, thereby improving lithium diffusion and ensuring high initial efficiency and capacity. Furthermore, when the primary particles are radially arranged, the pores exposed on the surface point towards the center of the secondary particles, thereby promoting lithium diffusion. Due to the radially arranged primary particles, uniform contraction and expansion are possible during lithium insertion / extraction and / or insertion / extraction. When lithium insertion / extraction occurs, pores exist in the (001) direction (which is the direction of particle expansion), thus acting as a buffer. Additionally, due to the size and arrangement of the primary particles, the possibility of cracks occurring during the contraction and expansion of the positive electrode active material is reduced, and the pores further mitigate volume changes, reducing cracks generated between primary particles during charging and discharging, thereby improving the cycle life characteristics of the rechargeable lithium battery and reducing resistance increase.

[0060] The positive electrode active material may have an irregular porous structure in at least one of the internal and external portions of the secondary particles. The term "irregular porous structure" refers to a structure in which the pore size and shape are irregular and non-uniform. For example, the secondary particles may include an internal portion containing an irregular porous structure and an external portion having a radially arranged structure. That is, unlike the primary particles in the external portion, the primary particles in the internal portion may be arranged irregularly. The internal portion containing an irregular porous structure includes primary particles similar to those in the external portion.

[0061] The ratio of the radius of the inner portion to the radius of the secondary particle (the distance from the center of the secondary particle to its surface) can be approximately 40% to approximately 60% of its length, and such a region can be defined as the inner portion. The outer portion can refer to the region extending from the outermost surface of the secondary particle to approximately 40% to approximately 60% of its radius. Furthermore, the ratio of the volume of the outer portion of the secondary particle to the volume of the secondary particle can be less than or equal to approximately 90% by volume, less than or equal to approximately 87% by volume, or less than or equal to approximately 85% by volume.

[0062] The secondary particles of the positive electrode active material may include radially arranged outer portions and an inner portion having an irregular porous structure, wherein the inner portion of the secondary particles may have pores larger than those of the outer portion. For example, in the positive electrode active material, the inner portion may have a pore size of about 150 nm to about 1 μm, and the outer portion may have a pore size smaller than about 150 nm. Thus, when the pore size of the inner portion is larger than that of the outer portion, compared to secondary particles with the same pore size in both the inner and outer portions, it has the advantage of shortening the diffusion distance of lithium in the active material, and lithium can be easily inserted from the outside. Additionally, it can have the effect of mitigating volume change during charging and discharging. In this document, when the pore is spherical or circular, the pore size refers to the average diameter; when the pore is elliptical, the pore size refers to the length of the major axis.

[0063] The secondary particles of the positive electrode active material may have openings on their surface facing the center of the internal portion, and the size of the openings may be less than about 150 nm, for example, about 10 nm to about 148 nm. The openings are pores with partially open walls, formed by the spaces between radially arranged plate-like primary particles, and connected to the center from the surface depth of the secondary particles. These openings may connect to the outside and can serve as channels through which matter can enter and exit. The openings may be formed at an average depth of less than or equal to about 150 nm from the surface of the secondary particles, for example, a depth of about 0.001 nm to about 100 nm, for example, a depth of about 1 nm to about 50 nm. The size and depth of the openings can be measured by the BJH (Barrett, Joyner, and Halenda) method, which is a method based on the adsorption or desorption content of nitrogen.

[0064] Closed pores may exist in the inner portion of the secondary particle, and closed pores and / or open pores may exist in the outer portion. Closed pores exclude or nearly exclude electrolytes, while open pores may contain electrolytes. Closed pores are independent pores not connected to other pores because all the walls of the pore are formed in a closed structure, while open pores are continuous pores connected to the outside of the secondary particle because at least some of the walls of the pore are formed in an open structure.

[0065] Figure 3 A schematic diagram illustrating the cross-sectional structure of the secondary particles in the positive electrode active material. (Reference) Figure 3 According to the embodiment, the secondary particles 11 of the positive electrode active material have an outer portion 14 (which has a structure in which plate-shaped primary particles are arranged in the radial direction) and an inner portion 12 (in which the primary particles 13 are irregularly arranged). The inner portion 12 may have more blank space between the primary particles than the outer portion 14. Furthermore, the pore size and porosity in the inner portion 12 are larger and more irregular compared to those in the outer portion 14. Figure 3 In the image, the arrows indicate the direction of lithium ion movement.

[0066] In the secondary particles, the inner portion 12 has a porous structure, which reduces the diffusion distance of lithium ions to the inner portion 12, and the outer portion 14 has a radial structure, which facilitates the embedding of lithium ions into the surface. Furthermore, due to the small size of the primary particles, lithium transfer paths between grains are easily ensured. Additionally, the small size of the primary particles and the porosity between them mitigate volume changes during charging and discharging, thus minimizing stress caused by volume changes during charging and discharging. This positive electrode active material can reduce the resistance of rechargeable lithium batteries and improve capacity and cycle life characteristics.

[0067] On the other hand, in the secondary particles, multiple primary particles can have a radial arrangement structure by arranging them toward a "single (1)" center to make surface contact along the thickness direction of the primary particles, or alternatively, the secondary particles can have a "multi-center" radial arrangement structure with multiple centers. As a result, when the secondary particles have a single-center radial arrangement structure or a multi-center radial arrangement structure, lithium is easily de-intercalated and / or intercalated into the center of the secondary particles.

[0068] Secondary particles may include radial primary particles and non-radial primary particles. Based on the total weight of radial and non-radial primary particles, the content of non-radial primary particles may be less than or equal to about 30 wt%, for example, from about 0.01 wt% to about 30 wt%, specifically from about 0.1 wt% to about 20 wt%.

[0069] Secondary particles include lithium-nickel composite oxides. Based on the total amount of metals other than lithium, the nickel content in lithium-nickel composite oxides can be greater than or equal to about 30 mol%, for example, greater than or equal to about 40 mol%, greater than or equal to about 50 mol%, greater than or equal to about 60 mol%, greater than or equal to about 70 mol%, greater than or equal to about 80 mol%, or greater than or equal to about 90 mol%, and less than or equal to about 99.9 mol% or less than or equal to about 99 mol%. For example, the nickel content in lithium-nickel composite oxides can be higher than the content of each of the other metals (such as cobalt, manganese, and aluminum). When the nickel content meets the above range, the positive electrode active material can exhibit excellent battery performance while achieving high capacity.

[0070] Lithium-nickel composite oxides can be represented by chemical formula 1.

[0071] [Chemical Formula 1]

[0072] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2-z X z,

[0073] In Chemical Formula 1, 0.9≤a1≤1.8, 0.3≤x1≤1, 0≤y1≤0.7, and 0≤z≤0.1, M 1 and M 2 are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr, or any combination thereof, and X is F, P, S, or any combination thereof.

[0074] In Chemical Formula 1, 0.4≤x1≤1 and 0≤y1≤0.6, 0.5≤x1≤1 and 0≤y1≤0.5, 0.6≤x1≤1 and 0≤y1≤0.4, 0.7≤x1≤1 and 0≤y1≤0.3, 0.8≤x1≤1 and 0≤y1≤0.2, or 0.9≤x1≤1 and 0≤y1≤0.1.

[0075] The lithium nickel-based composite oxide may be represented by, for example, Chemical Formula 2.

[0076] [Chemical Formula 2]

[0077] Li a2 Ni x2 Co y2 M 3 1-x2-y2 O 2-z X z ,

[0078] In Chemical Formula 2, 0.9≤a2≤1.8, 0.3≤x2<1, 0<y2≤0.7, and 0≤z≤0.1, M 3 is Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr, or any combination thereof, and X is F, P, S, or any combination thereof.

[0079] In Chemical Formula 2, 0.3≤x2≤0.99 and 0.01≤y2≤0.7, 0.4≤x2≤0.99 and 0.01≤y2≤0.6, 0.5≤x2≤0.99 and 0.01≤y2≤0.5, 0.6≤x2≤0.99 and 0.01≤y2≤0.4, 0.7≤x2≤0.99 and 0.01≤y2≤0.3, 0.8≤x2≤0.99 and 0.01≤y2≤0.2, or 0.9≤x2≤0.99 and 0.01≤y2≤0.1.

[0080] The lithium nickel-based composite oxide may be represented by, for example, Chemical Formula 3.

[0081] [Chemical Formula 3]

[0082] Li a3 Ni x3 Co y3 M 4 z3 M 5 1-x3-y3-z3 O 2-z X z ,

[0083] In chemical formula 3, 0.9 ≤ a³ ≤ 1.8, 0.3 ≤ x³ ≤ 0.98, 0.01 ≤ y³ ≤ 0.69, 0.01 ≤ z³ ≤ 0.69, 0 ≤ z ≤ 0.1, M 4 For Al, Mn, or any combination thereof, M 5 X is B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W, Zr or any combination thereof, and X is F, P, S or any combination thereof.

[0084] In chemical formula 3, 0.4≤x3≤0.98, 0.01≤y3≤0.59 and 0.01≤z3≤0.59, 0.5≤x3≤0.98, 0.01≤y3≤0.49 and 0.01≤z3≤0.49, 0.6≤x3≤0.98, 0.01≤y3≤0.39 and 0.01≤z3≤0.39, 0.7≤x3≤0.98, 0.01≤y3≤0.29 and 0.01≤z3≤0.29, 0.8≤x3≤0.98, 0.01≤y3≤0.19 and 0.01≤z3≤0.19, or 0.9≤x3≤0.98, 0.01≤y3≤0.09 and 0.01≤z3≤0.09.

[0085] Generally speaking, as the nickel content in the positive electrode active material increases, due to the Ni content... 2+ Increased cation mixing with lithium ions can actually reduce capacity, or impurities (such as NiO) can hinder lithium ion diffusion, leading to deteriorated cycle life. Furthermore, structural collapse and cracking during charging and discharging can cause side reactions between the positive electrode active material and the electrolyte, potentially reducing cycle life and posing safety risks. To address these issues, in conventional methods, when boron is only coated on the surface of the positive electrode active material, boron acts as a resistor, actually reducing capacity and deteriorating cycle life. Conversely, the positive electrode active material according to the embodiment, while using a high-nickel material, appropriately and correspondingly includes a boron coating and a boron doping layer, thus mitigating the problems caused by high nickel concentration, achieving high capacity, and improving cycle life characteristics without deteriorating the initial discharge capacity.

[0086] Methods for preparing positive electrode active materials

[0087] In one embodiment, a method for preparing a positive electrode active material for a rechargeable lithium battery includes mixing a nickel hydroxide, a lithium feedstock, and a boron feedstock, and then heat-treating the resulting product.

[0088] Conventionally, when coating boron onto a positive electrode active material, lithium raw material is typically mixed with a nickel hydroxide, followed by heat treatment to prepare a lithium-nickel composite oxide. A boron source is then mixed with this oxide using a wet or dry method, followed by another heat treatment. In this case, only the surface of the positive electrode active material is coated with boron, thus the boron acts as a resistor, reducing capacity and cycle life. On the other hand, the preparation method according to the embodiment produces secondary particles in which at least a portion of the primary particles are radially arranged. Simultaneously, a boron coating and a boron doping layer are appropriately formed, so that boron does not act as a resistor, resulting in a positive electrode active material with structural stability and excellent cycle life characteristics.

[0089] In the preparation method, nickel hydroxide is a precursor of the positive electrode active material, and can be represented as nickel metal composite hydroxide or nickel transition metal composite hydroxide, and can be prepared by co-precipitation method, etc.

[0090] Nickel hydroxides can be represented, for example, by chemical formula 11.

[0091] [Chemical Formula 11]

[0092] Ni x11 M 11 y11 M 12 1-x11-y11 (OH)2,

[0093] In chemical formula 11, 0.3 ≤ x11 ≤ 1, 0 ≤ y11 ≤ 0.7, and M 11 and M 12 Each of the following is independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or any combination thereof.

[0094] As a specific example, nickel hydroxides can be represented by chemical formula 12 or chemical formula 13.

[0095] [Chemical Formula 12]

[0096] Ni x12 Co y12 M 13 1-x12-y12 (OH)2,

[0097] In chemical formula 12, 0.3 ≤ x12 < 1, 0 <y12≤0.7,M 13It is Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr or any combination thereof.

[0098] [Chemical Formula 13]

[0099] Ni x13 Co y13 M 14 z13 M 15 1-x13-y13-z13 (OH)2,

[0100] In chemical formula 13, 0.3 ≤ x13 ≤ 0.98, 0.01 ≤ y13 ≤ 0.69, 0.01 ≤ z13 ≤ 0.69, M 14 For Al, Mn, or any combination thereof, and M 15 It is B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr or any combination thereof.

[0101] The lithium raw material can be, for example, lithium hydroxide, and can be mixed in a ratio of about 0.8 mol to about 1.8 mol or about 0.8 mol to about 1.2 mol based on 1 mol of nickel hydroxide.

[0102] Boron raw materials can be boron-containing compounds, such as H3BO3, HBO2, B2O3, C6H5B(OH)2, (C6H5O)3B, [CH3(CH2)3O]3B, (C3H7O)3B, C3H9B3O6, C 13 H 19 BO3 or any combination thereof.

[0103] Based on 100 molar parts of nickel hydroxide, the boron content can be from about 0.1 molar parts to about 5 molar parts, for example, about 0.1 molar parts to about 4 molar parts, about 0.1 molar parts to about 3 molar parts, about 0.1 molar parts to about 2.9 molar parts, about 0.1 molar parts to about 2.5 molar parts, about 0.1 molar parts to about 2 molar parts, about 0.1 molar parts to about 1.5 molar parts, or about 0.5 molar parts to about 1.3 molar parts. When the boron content meets the above range, boron does not act as a resistor in the positive electrode active material and can be used to improve the performance of rechargeable lithium batteries, thereby improving capacity and cycle life characteristics. When the boron content is too high, the boron coating content increases excessively, and boron acts as a resistor in the positive electrode active material, thereby reducing battery capacity and cycle life.

[0104] The heat treatment can be performed at temperatures ranging from approximately 650°C to approximately 850°C or from approximately 690°C to approximately 780°C. Under these conditions, a positive electrode active material for rechargeable lithium batteries with a stable structure comprising both a boron coating and a boron doping layer can be prepared.

[0105] In addition, the heat treatment can be carried out for approximately 5 to approximately 25 hours, for example, approximately 8 to approximately 12 hours. Under this condition, a positive electrode active material for rechargeable lithium batteries with a stable structure, including both a boron coating and a boron doping layer, is prepared.

[0106] In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include a binder and / or a conductive material.

[0107] The binder improves the adhesion properties between the positive electrode active material particles and between them and the positive electrode current collector. Examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic styrene-butadiene rubber, epoxy resin, and nylon, but are not limited to these.

[0108] Based on the total weight of the positive electrode active material layer, the binder content in the positive electrode active material layer can be approximately 1 wt% to approximately 5 wt%.

[0109] Conductive materials are included to provide electrode conductivity. Any electrically conductive material may be used as a conductive material unless it causes a chemical change. Examples of conductive materials may include carbon-based materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes); metallic materials including metal powders or fibers of metals such as copper, nickel, aluminum, and silver; conductive polymers (such as polyphenylene derivatives); or mixtures thereof.

[0110] Based on the total weight of the positive electrode active material layer, the content of conductive material in the positive electrode active material layer can be approximately 1 wt% to approximately 5 wt%.

[0111] Aluminum foil can be used as a positive electrode current collector, but is not limited to this.

[0112] negative electrode

[0113] The negative electrode for a rechargeable lithium battery may include, for example, a negative electrode current collector and a layer of negative electrode active material on the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material and may further include a binder and / or a conductive material.

[0114] The negative electrode active material may include a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.

[0115] The material capable of reversibly intercalating / deintercalating lithium ions may include, for example, crystalline carbon, amorphous carbon, or any combination thereof as a carbon-based negative electrode active material. The crystalline carbon may be amorphous, flake-like, scaly, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonized products, calcined coke, and the like.

[0116] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0117] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite material, SiO x (0<x<2), a Si-Q alloy (where Q is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element other than Si, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or any combination thereof), and the Sn-based negative electrode active material may include Sn, SnO₂, a Sn-R alloy (where R is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element other than Sn, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or any combination thereof). At least one of these materials may be mixed with SiO₂. Elements Q and R may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and any combination thereof.

[0118] The silicon-carbon composite material can be, for example, a silicon-carbon composite material comprising a core containing crystalline carbon and silicon particles, and an amorphous carbon coating disposed on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or any combination thereof. The amorphous carbon precursor can be coal tar pitch, mesophase pitch, petroleum tar pitch, coal oil, petroleum heavy oil, or polymer resin (such as phenolic resin, furan resin, or polyimide resin). In this case, the silicon content can be from about 10 wt% to about 50 wt% based on the total weight of the silicon-carbon composite material. Additionally, the crystalline carbon content can be from about 10 wt% to about 70 wt% based on the total weight of the silicon-carbon composite material, and the amorphous carbon content can be from about 20 wt% to about 40 wt% based on the total weight of the silicon-carbon composite material. Furthermore, the thickness of the amorphous carbon coating can be from about 5 nm to about 100 nm. The average particle size (D50) of the silicon particles can be from about 10 nm to about 20 μm. The average particle size (D50) of the silicon particles is preferably from about 10 nm to about 200 nm. Silicon particles can exist in an oxidized form, in which case the atomic ratio of Si:O in the silicon particles, indicating the degree of oxidation, can be approximately 99:1 to approximately 33:67. The silicon particles can be SiO₂. x Particles, in this case, SiO x The range of x can be greater than about 0 and less than about 2. As used herein, unless otherwise specified, the average particle size (D50) indicates the diameter of particles that constitute about 50% of the cumulative volume in the particle distribution.

[0119] Si-based or Sn-based anode active materials can be mixed with carbon-based anode active materials. When mixing and using Si-based or Sn-based anode active materials and carbon-based anode active materials, the mixing ratio can be approximately 1:99 to approximately 90:10 by weight.

[0120] In the negative electrode active material layer, the amount of negative electrode active material included, based on the total weight of the negative electrode active material layer, can be approximately 95 wt% to approximately 99 wt%.

[0121] In an embodiment, the negative electrode active material layer may further include a binder, and optionally further include a conductive material. Based on the total weight of the negative electrode active material layer, the binder content in the negative electrode active material layer may be from about 1 wt% to about 5 wt%. Alternatively, when further including a conductive material, the negative electrode active material layer may include about 90 wt% to about 98 wt% of the negative electrode active material, about 1 wt% to about 5 wt% of the binder, and about 1 wt% to about 5 wt% of the conductive material.

[0122] The binder is used to ensure good adhesion between the negative electrode active material particles and also to adhere the negative electrode active material to the negative electrode current collector. The binder may be a water-insoluble binder, a water-soluble binder, or any combination thereof.

[0123] Examples of water-insoluble adhesives include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, ethylene propylene copolymers, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or any combination thereof.

[0124] Water-soluble adhesives may include rubber adhesives or polymeric resin adhesives. Rubber adhesives may be selected from styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and any combination thereof. Polymeric resin adhesives may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and any combination thereof.

[0125] When a water-soluble binder is used as a negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity as a thickener. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and their alkali metal salts may be mixed and used. As an alkali metal, Na, K, or Li may be used. Based on 100 parts by weight of the negative electrode active material, the amount of this thickener may be from about 0.1 parts by weight to about 3 parts by weight.

[0126] Conductive materials are included to provide electrode conductivity. Any electrically conductive material can be used as a conductive material unless it causes a chemical change. Examples of conductive materials include carbon-based materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes); metallic materials including metal powders or fibers of copper, nickel, aluminum, silver, etc.; conductive polymers (such as polyphenylene derivatives); or mixtures thereof.

[0127] The negative current collector may include one selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with conductive metal, and any combination thereof.

[0128] electrolytes

[0129] The electrolyte according to the embodiment includes vinylene carbonate (VC). It is believed that the vinylene carbonate in the electrolyte generates a large amount of gas only during overvoltage charging due to its combination with the positive electrode active material according to the embodiment, and no gas is generated within the normal voltage range.

[0130] Based on the total weight of the electrolyte, the amount of vinylene carbonate included can be from about 0.1 wt% to about 5 wt%, for example, from about 0.2 wt% to about 4 wt%, from about 0.5 wt% to about 3 wt%, or from about 0.8 wt% to about 2 wt%. When vinylene carbonate is included in the above range, safety can be ensured by increasing the amount of gas generated during overcharging, while improving the general performance of the battery, such as cycle life characteristics.

[0131] In addition to vinylene carbonate, electrolytes may further include non-aqueous organic solvents and lithium salts.

[0132] In this paper, based on the total weight of 100 parts by weight of non-aqueous organic solvent and lithium salt, the content of vinylene carbonate may be about 0.1 parts by weight to about 5 parts by weight, about 0.3 parts by weight to about 4 parts by weight, about 0.5 parts by weight to about 3 parts by weight, or about 0.8 parts by weight to about 2 parts by weight.

[0133] Non-aqueous organic solvents are used as media for transporting ions involved in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, or aprotic solvents. Carbonate solvents can include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene glycol carbonate (EC), propylene glycol carbonate (PC), and butylene glycol carbonate (BC), etc. Ester solvents can include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolactone, valerate, mevalonolactone, and caprolactone, etc. Ether solvents can include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran, etc. Ketone solvents can include cyclohexanone, etc. In addition, alcohol solvents may be ethanol, isopropanol, etc., and aprotic solvents may be nitriles (such as R-CN, where R is a C2 to C20 straight chain, branched chain or cyclic hydrocarbon group, and may include double bond, aromatic ring or ether bond), amides (such as dimethylformamide), dioxolane (such as 1,3-dioxolane) and sulfolane, etc.

[0134] It can be used alone or in mixtures with non-aqueous organic solvents. When using non-aqueous organic solvents in mixtures, the mixture ratio can be controlled according to the desired battery performance.

[0135] Alternatively, in the case of carbonate solvents, a mixture of cyclic carbonates and linear carbonates can be used. In this case, when cyclic carbonates and linear carbonates are mixed in a volume ratio of about 1:1 to about 1:9, the electrolyte exhibits excellent performance.

[0136] In addition to carbonate solvents, non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. In this case, carbonate solvents and aromatic hydrocarbon organic solvents can be mixed in a volume ratio of about 1:1 to about 30:1.

[0137] As an aromatic hydrocarbon solvent, aromatic hydrocarbon compounds represented by chemical formula I can be used.

[0138] [Chemical Formula I]

[0139]

[0140] In chemical formula I, R 4 ~R 9 They may be the same or different and are selected from hydrogen, halogens, C1 to C10 alkyl groups, haloalkyl groups and any combination thereof.

[0141] Specific examples of aromatic hydrocarbon solvents can be selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, and fluorotoluene. 2,3-Difluorotoluene, 2,4-Difluorotoluene, 2,5-Difluorotoluene, 2,3,4-Trifluorotoluene, 2,3,5-Trifluorotoluene, Chlorotoluene, 2,3-Dichlorotoluene, 2,4-Dichlorotoluene, 2,5-Dichlorotoluene, 2,3,4-Trichlorotoluene, 2,3,5-Trichlorotoluene, Iodotoluene, 2,3-Diiodotoluene, 2,4-Diiodotoluene, 2,5-Diiodotoluene, 2,3,4-Triiodotoluene, 2,3,5-Triiodotoluene, Xylene, and any combination thereof.

[0142] The electrolyte may further include ethylene glycol carbonate compounds of formula II in order to improve the cycle life of the battery.

[0143] [Chemical Formula II]

[0144]

[0145] In chemical formula II, R 10 and R 11 The same or different, and selected from hydrogen, halogen, cyano, nitro and fluorinated C1 to C5 alkyl groups, under the condition that R 10 and R 11 At least one of them is selected from halogen, cyano, nitro and fluorinated C1-C5 alkyl groups, but R 10 and R 11 Not all of them are hydrogen.

[0146] Examples of ethylene glycol carbonate compounds may be difluoroethylene glycol carbonate, chloroethylene glycol carbonate, dichloroethylene glycol carbonate, bromoethylene glycol carbonate, dibromoethylene glycol carbonate, nitroethylene glycol carbonate, cyanoethylene glycol carbonate, or fluoroethylene glycol carbonate. The amount of additives used to improve cycle life may be used within appropriate limits.

[0147] Lithium salts dissolved in non-aqueous organic solvents supply lithium ions to the battery, ensuring the basic operation of the rechargeable lithium battery and improving the transport of lithium ions between the positive and negative electrodes.

[0148] Examples of lithium salts include at least one carrier salt selected from the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are natural numbers, for example, integers ranging from 1 to 20), lithium difluoro(bis(oxalate)phosphate), LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalate)borate, LiBOB) and lithium difluoro(oxalate)borate (LiDFOB).

[0149] Lithium salts can be used at concentrations ranging from approximately 0.1 M to approximately 2.0 M. When lithium salts are included in the above concentration range, the electrolyte exhibits excellent performance and lithium-ion mobility due to its optimal electrolyte conductivity and viscosity.

[0150] diaphragm

[0151] The separator separates the positive and negative electrodes and provides a transport channel for lithium ions, and can be any commonly used separator in lithium-ion batteries. In other words, it can have low resistance to ion transport and excellent impregnation properties with the electrolyte. For example, the separator material can be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene, or any combination thereof. It can be in the form of non-woven or woven fabric. For example, in lithium-ion batteries, polyolefin polymers (such as polyethylene and polypropylene) can be used primarily as the separator material. To ensure heat resistance or mechanical strength, coated separators including ceramic components or polymer materials can be used. Optionally, it can have a single-layer or multi-layer structure.

[0152] Rechargeable lithium battery

[0153] Figure 4 A schematic diagram illustrating a rechargeable lithium battery according to an embodiment. (Reference) Figure 4 The rechargeable lithium battery 100 according to an embodiment includes: a positive electrode 114; a negative electrode 112 facing the positive electrode 114; a separator 113 between the positive electrode 114 and the negative electrode 112; an electrolyte impregnated with the positive electrode 114, the negative electrode 112 and the separator 113; a housing 120 containing the positive electrode 114, the negative electrode 112, the separator 113 and the electrolyte; and a sealing member 140 sealing the housing 120.

[0154] Additionally, rechargeable lithium batteries may incorporate an overcharge safety device within the casing. This overcharge safety device may be, for example, a device that triggers a short circuit when the battery's internal pressure exceeds a predetermined value (i.e., a pressure-responsive short-circuit device) or a pressure-responsive open-circuit device that triggers an open circuit when the battery's internal pressure exceeds a predetermined value. For example, when the internal pressure of the rechargeable lithium battery is greater than or equal to approximately 7 kgf / cm²... 2 The overcharge safety device can be activated at this time.

[0155] A pressure-responsive open-circuit device is a current-interrupting device that blocks charging when the internal pressure of the battery reaches a predetermined value or higher due to problems such as the battery temperature reaching a predetermined value or higher, or the battery voltage reaching a predetermined value or higher. The pressure-responsive open-circuit device can be configured, for example, to cause a metal plate on the outer wall of the casing to expand upwards when the internal pressure of the battery rises excessively, thereby blocking both external and internal circuits. According to the embodiment, the rechargeable lithium battery rapidly generates gas during overcharging, causing the open-circuit device to operate quickly, thus preventing further charging and effectively blocking overcharging.

[0156] Due to issues such as the battery temperature reaching a predetermined value or higher, or the battery voltage being greater than or equal to a predetermined value, a pressure-responsive short-circuit device can trigger an internal short circuit and cause the electrodes to discharge when the gas pressure inside the battery reaches a predetermined value or higher. The pressure-responsive short-circuit device can, for example, be configured to create a short circuit between the positive and negative electrodes when the internal pressure of the battery excessively increases, causing a metal plate attached to the outer wall of the casing to expand upwards and contact a portion with a different potential. The rechargeable lithium battery according to the embodiment effectively prevents overcharging because gas is rapidly generated in the battery during overvoltage charging, causing the pressure-responsive short-circuit device to operate rapidly and discharge the electrode plates. When the pressure-responsive short-circuit device is applied, the rechargeable lithium battery may further include thermally operated devices (TCOs), such as fuses, positive thermal circuit breakers (PTCs), bimetallic strips, and circuit breakers, to control heat generation due to discharge.

[0157] Rechargeable lithium batteries can be classified as lithium-ion batteries, lithium-ion polymer batteries, lithium polymer batteries, or all-solid-state batteries, depending on the presence or absence of a separator and the type of electrolyte. Based on shape, rechargeable lithium batteries can be categorized as cylindrical, square, coin-shaped, and pouch-shaped, etc. The structures and manufacturing methods for lithium-ion batteries disclosed herein are well known in the art.

[0158] Due to its high capacity, improved storage stability and cycle life characteristics at high temperatures, high rate capability, and improved overcharge safety, the rechargeable lithium battery according to the embodiments can be used in electric vehicles (EVs) or hybrid vehicles (such as plug-in hybrid electric vehicles (PHEVs)).

[0159] The following describes embodiments and comparative examples of the present invention. However, it should be understood that the embodiments are for illustrative purposes and are not intended to limit the invention.

[0160] Example 1

[0161] Preparation of positive electrode active material precursor

[0162] The precursor for the positive electrode active material was prepared by the following co-precipitation method. Nickel sulfate, cobalt sulfate, and aluminum nitrate were used as metal raw materials. Additionally, ammonia (NH4OH) and sodium hydroxide (NaOH) were prepared as precipitating agents to form a complex.

[0163] Step 1: 1.5kW / m 3 [NH4OH 0.35M, pH 11.5–11.7 and reaction time 6 hours]

[0164] First, 0.35M ammonia solution is added to the reactor. At a power output of 1.5 kW / m³... 3 The reaction was initiated at 50°C with the addition of the metal raw material and NH4OH at 85 ml / min and 9 ml / min, respectively, while stirring. NaOH was added to maintain the pH, and the reaction was carried out for 6 hours. As a result, the average size of the obtained core particles was confirmed to be in the range of approximately 6.5 μm to 7.5 μm, and the second step was carried out as follows.

[0165] Step 2: 1.0kW / m 3 [NH4OH 0.40M, pH 11.5–11.7 and reaction time 16 hours]

[0166] The metal feedstock and NH4OH were added at 107 ml / min and 13 ml / min respectively, while the reaction temperature was maintained at 50 °C to keep the NH4OH concentration at 0.40 M. NaOH was added to maintain the pH, and the reaction proceeded for 16 hours. At this point, the stirring power was reduced to 1.0 kW / m. 3 (At a stirring power lower than in the first step), and the reaction continues. By conducting this reaction, the average size of the product particles containing the core and intermediate layer was confirmed to be 10.5 μm to 11.5 μm, and the third step was carried out as follows.

[0167] Step 3: 0.5kW / m 3 [NH4OH 0.40M, pH 11.5–11.7 and reaction time 5 hours]

[0168] While maintaining a reaction temperature of 50°C, the metal raw material and NH4OH were added at rates of 142 ml / min and 17 ml / min, respectively, to keep the NH4OH concentration the same as in the second step. NaOH was added to maintain the pH, and the reaction proceeded for 5 hours, resulting in an average particle size of 14 μm. At this point, the stirring power was reduced to 0.5 kW / m. 3 (This is lower than the stirring power in the second step), and the reaction continues.

[0169] [Post-processing]

[0170] After rinsing, the product was dried with hot air at approximately 150°C for 24 hours to obtain nickel hydroxide (Ni 0.945 Co 0.04 Al 0.015 (OH)2), which is a precursor of positive electrode active material. Figure 5 This is a SEM image of the cross-section of the positive electrode active material precursor prepared in Example 1.

[0171] 2. Preparation of positive electrode active material

[0172] The obtained nickel hydroxide and LiOH were mixed in a 1:1 molar ratio, and 1.0 molar of boric acid was added based on 100 molar parts of nickel hydroxide. Then, the mixture was heat-treated at 725°C for 10 hours under an oxygen atmosphere to obtain the positive electrode active material (LiNi). 0.945 Co 0.04 Al 0.015 O2). Figure 6 This is a SEM image of the cross-section of the positive electrode active material prepared in Example 1. (Reference) Figure 6The positive electrode active material has a secondary particle structure, in which multiple primary particles are aggregated. The primary particles are arranged radially, and the porous center is located in the secondary particle structure.

[0173] 3. Manufacturing of the positive electrode

[0174] 96 wt% of the obtained positive electrode active material, 2 wt% of polyvinylidene fluoride, 2 wt% of carbon nanotubes, and N-methylpyrrolidone as a solvent were mixed in a mixer to prepare a slurry for the positive electrode active material layer. The slurry for the positive electrode active material layer was coated onto aluminum foil to form an electrode plate, dried at 135°C for 3 hours or longer, and then extruded and vacuum dried to manufacture the positive electrode.

[0175] 4. Manufacturing of the negative electrode

[0176] A negative electrode active material slurry was prepared by mixing 97.3 wt% graphite, 0.5 wt% Denca Black, 0.9 wt% carboxymethyl cellulose, and 1.3 wt% styrene-butadiene rubber as the negative electrode active material in an aqueous solvent. The negative electrode active material slurry was coated onto copper foil, dried, and extruded to manufacture the negative electrode.

[0177] 5. Manufacturing of individual battery cells

[0178] A rechargeable lithium-ion battery cell is manufactured by sequentially stacking a positive electrode, a separator with a polyethylene / polypropylene multilayer structure, and a negative electrode, then housing them in a casing equipped with an overcharge safety device, and finally injecting an electrolyte into the casing. The electrolyte is prepared by adding 1.5 parts by weight of vinylene carbonate to 100 parts by weight of an electrolyte solution, which is prepared by adding 1.1 M LiPF6 lithium salt to a solvent of ethylene glycol carbonate, ethyl methyl carbonate, and dimethyl carbonate mixed in a volume ratio of 2:4:4.

[0179] Comparative Example 1

[0180] By using LiNi composed of typical secondary particles with a particle size of approximately 14 μm... 0.945 Co 0.04 Al 0.015 O2 was mixed with 3 mol% cobalt oxide, and the mixture was then heat-treated in a furnace at approximately 700°C for 15 hours under an oxygen atmosphere, and then cooled to room temperature to prepare a positive electrode active material consisting of cobalt-coated secondary particles. The positive electrode, negative electrode, and battery cell were manufactured using essentially the same method as in Example 1, except that the above-described positive electrode active material from Comparative Example 1 was used.

[0181] Comparative Example 2

[0182] The positive electrode active material, positive electrode, negative electrode, and battery cell were manufactured using essentially the same method as in Example 1, except that the positive electrode active material (LiNi) was prepared without adding boric acid, i.e., without boron coating. 0.945 Co 0.04 Al 0.015 O2).

[0183] Comparative Example 3

[0184] By using 100 moles of the positive electrode active material (LiNi) from Comparative Example 2 0.945 Co 0.04 Al 0.015 O2) was mixed with 1.0 molar of boric acid, and then the mixture was heat-treated at about 350°C for 8 hours in an oxygen atmosphere to coat a boron compound in a conventional manner to prepare a positive electrode active material. The positive electrode and battery cell were manufactured in essentially the same manner as in Example 1, except that this positive electrode active material of Comparative Example 3 was used.

[0185] Evaluation Example 1: Evaluation of Boron Coating

[0186] Figure 7 The image shows a ToF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) analysis of the surface of the positive electrode active material in Example 1. Figure 8 for Figure 7 Mass spectrometry results from ToF-SIMS analysis. Figure 7 This shows that boron is uniformly distributed on the surface of the positive electrode active material, and Figure 8 The discovery of boron compounds in the form of BO2 is shown. Accordingly, a boron coating comprising lithium borate is uniformly applied to the surface of the positive electrode active material of Example 1, wherein lithium borate (such as LiBO2) is the main component.

[0187] Evaluation Example 2: Confirmation of Boron Doping Layer by TEM-EELS Analysis

[0188] Figure 9 This is a TEM image of the primary particles (i.e., the outermost portion of the primary particles in the positive electrode active material of Example 1, exposed on the surface of the secondary particles). Figure 9 Electron energy loss spectroscopy (EELS) was performed at a total of 10 points, from point 1 to point 10, as marked in the figure. The results are shown in... Figure 10 In. For example, in Figure 10 In the diagram, ① is the analysis diagram at point 1. (See reference) Figure 10 In the figure below, cobalt was detected starting from point 4, i.e., from point 4 to point 10. Correspondingly, the starting point of the active material's surface could be approximately point 4. (Reference) Figure 10In the figure above, boron was detected from point 3 to point 8. In this paper, the boron detected at point 3 could be from a boron coating on the surface of the active material, while the boron from points 4 to 8 comes from the inside of the active material, indicating that the boron inside the active material is a very thin boron-doped layer.

[0189] Evaluation Example 3: Evaluation of boron content in boron coatings and boron-coated areas at grain boundaries

[0190] The positive electrode active material prepared in Example 1 was subjected to ICP (inductively coupled plasma) emission spectroscopy analysis to measure the boron content. Then, 10 g of each positive electrode active material was added to 100 g of distilled water, stirred for 30 minutes, and filtered through a filter to obtain the positive electrode active material. This rinsing process completely removed boron from the surface of the positive electrode active material. The recovered positive electrode active material was dried at 130°C for 24 hours, and then the remaining boron content in the positive electrode active material was measured again by ICP emission spectroscopy analysis. This boron content is expressed as the boron content of the "internal portion," which refers to the content of the boron-coated portion at the grain boundaries.

[0191] Additionally, the difference between the boron content before and after rinsing, obtained by subtracting the boron content after rinsing from the boron content before rinsing, i.e., the boron content removed by rinsing, is expressed as the boron content of the "external portion." This refers to the boron content of the boron coating.

[0192] The boron content of the internal and external portions of the positive electrode active material of the examples prepared using essentially the same method as in Example 1 (except that the amount of boric acid added (1.0 mol in Example 1) was changed to 0 mol, 0.5 mol, 1.5 mol, 3.0 mol, and 5.0 mol) was analyzed. The results showed that... Figure 11 In. Figure 11 In this context, the unit ppm can indicate 10 -4 wt%, which is the weight ratio of boron to the total weight of the positive electrode active material.

[0193] refer to Figure 11 Example 1, in which the boron input is 1.0 molar, shows an external boron (boron coating) amount of approximately 1000 ppm (i.e., 0.1 wt% based on the total amount of the positive electrode active material) and an internal boron (grain boundary boron coating portion) amount of approximately 50 ppm (i.e., 0.005 wt% based on the total amount of the positive electrode active material). In this document, the weight ratio of boron in the internal portion to boron in the external portion is calculated to be approximately 95:5. Furthermore, in Figure 11 In this study, when the boron input was 1.5 moles, the calculated boron weight ratio of the internal portion to the external portion was approximately 92:8. (Reference) Figure 11 Boron compounds (such as lithium borate) are coated onto the internal grain boundaries and the surface of secondary particles of the positive electrode active material, wherein the boron content on the surface is four times or more than the boron content on the internal grain boundaries.

[0194] Evaluation Example 4: 5V Overcharge Evaluation

[0195] The battery cells according to Comparative Examples 1 to 3 and Example 1 were charged to 5.0V at a constant current rate of 0.5C at 25°C and cut off at a rate of 0.1C in constant voltage mode. In this paper, the gas emission (cc / g) per unit weight of positive electrode active material in the battery cells was measured, and the results are shown in... Figure 12 As for the overcharge C rate, based on the evaluated capacity, the capacity is measured by charging at a constant current to 4.3V at a 0.2C rate, charging at a constant voltage to a current of 0.05C, then pausing for 10 minutes, and discharging at a constant current at a 0.2C rate to 3V as a reference for the 1C rate.

[0196] refer to Figure 12 During a 5V overcharge, Example 1 showed a gas emission of 3.4 cc / g per unit weight of positive electrode active material, which is significantly greater than the 1.7 cc / g or less of Comparative Examples 1 to 3. Accordingly, it is anticipated that in the event of overcharging, the battery cell of Example 1 will ensure safety by rapidly activating the safety device.

[0197] In addition, the positive electrode active material has a 0.6m 2 Comparative Example 3, with a high specific surface area of ​​ / g or greater, shows a lower gas emission than that of Example 1. Therefore, as the specific surface area of ​​the positive electrode active material increases, there is not enough effect in terms of gas emission.

[0198] Evaluation Example 5: Current Evaluation During Overvoltage Charging

[0199] The positive electrode plate from Example 1 was stamped into a 14mm circle to serve as the positive electrode, and lithium foil was used as the negative electrode to form a three-electrode cup-shaped battery cell. An electrolyte containing vinylene carbonate was placed in this cup in essentially the same manner as in Example 1, and this was designated Example 2. The current change of the battery cell of Example 2 was examined while the voltage was increased at a constant rate.

[0200] Furthermore, the battery cell of Comparative Example 4 was prepared in essentially the same manner as in Example 2, except that an electrolyte excluding vinylene carbonate was used. Additionally, the battery cell of Reference Example A was prepared in essentially the same manner as in Example 2, except that LiBO2 was used as the positive electrode instead of the positive electrode in Example 2. Furthermore, the battery cell of Reference Example B was prepared in essentially the same manner as in Reference Example A, except that an electrolyte excluding vinylene carbonate was used.

[0201] The current of the battery cells in Example 2, Comparative Example 4, and Reference Examples A and B was measured by increasing the voltage from 3V to 6V at a constant rate of 0.1mV / second at 25°C. The results show that... Figure 13 middle.

[0202] refer to Figure 13 Comparative Example 4, excluding vinylene carbonate, showed that at abnormal voltages of 4.7V or higher, the current did not increase, but only tended to increase after 5.2V. On the other hand, Example 2 showed that the current increased rapidly from about 4.7V, but remained constant after 5.0V.

[0203] Furthermore, Reference Example A demonstrates a rapid increase in current starting from approximately 4.7V, but Reference Example B, excluding vinylene carbonate, demonstrates no current change up to 6V. Correspondingly, as... Figure 12 The increased gas emissions shown at 4.7V or higher voltages confirm that the effect is due to the lithium borate of the positive electrode and the vinylene carbonate included in the electrolyte, rather than the effect of specific surface area.

[0204] Although this disclosure has been described in conjunction with exemplary embodiments now considered to be in practice, it is to be understood that the invention is not limited to the disclosed embodiments. Rather, it is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

Claims

1. A rechargeable lithium battery, comprising: A positive electrode comprising a positive electrode active material, the positive electrode active material comprising secondary particles and a boron coating comprising lithium borate disposed on the surface of the secondary particles, wherein a plurality of primary particles are aggregated in the secondary particles, and the secondary particles have at least a portion of the primary particles arranged radially, the secondary particles comprising a lithium nickel composite oxide, the positive electrode active material further comprising a grain boundary boron coating portion, the grain boundary boron coating portion being disposed on the surface of the primary particles inside the secondary particles and comprising lithium borate; negative electrode; A membrane between the positive electrode and the negative electrode; Electrolytes including vinylene carbonate; and A casing containing the positive electrode, the negative electrode, the diaphragm, and the electrolyte. Based on the total weight of the positive electrode active material, the content of the boron coating is 0.02 wt% to 0.5 wt%, and the content of the intergranular boron coating portion is 0.001 wt% to 0.05 wt%.

2. The rechargeable lithium battery according to claim 1, wherein... During a 5V overcharge, the amount of gas emitted per unit weight of the positive electrode active material in the rechargeable lithium battery is greater than or equal to 3.0 cc / g.

3. The rechargeable lithium battery according to claim 1, wherein... The housing is provided with an overcharge safety device.

4. The rechargeable lithium battery according to claim 3, wherein... The overcharge safety device is a device that triggers an open circuit when the internal pressure of the rechargeable lithium battery reaches a predetermined value or higher, or a device that triggers a short circuit when the internal pressure of the rechargeable lithium battery reaches the predetermined value or higher.

5. The rechargeable lithium battery according to claim 3, wherein... When the internal pressure of the rechargeable lithium battery is greater than or equal to 7 kgf / cm 2 When this occurs, the overcharge safety device operates.

6. The rechargeable lithium battery according to claim 1, wherein... Based on the total weight of the electrolyte, the amount of vinylene carbonate included is 0.1 wt% to 5 wt%.

7. The rechargeable lithium battery according to claim 1, wherein... In the positive electrode active material, the lithium borate of the boron coating includes LiBO2 and Li3B7O. 12 Li6B4O9, Li3B 11 O 18 Li₂B₄O₇, Li₃BO₃, Li₈B₆O 13 Li5B3O7, Li4B2O5, Li 10 B4O 11 Li8B2O7 or any combination thereof.

8. The rechargeable lithium battery according to claim 1, wherein... Based on the positive electrode active material, the content of lithium borate in the boron coating is 0.02 wt% to 0.5 wt%.

9. The rechargeable lithium battery according to claim 1, wherein... The positive electrode active material further includes a boron-doped layer exposed on the surface of the secondary particles inside the primary particles.

10. The rechargeable lithium battery according to claim 9, wherein... The boron-doped layer is disposed at a depth of 10 nm from the outer surface of the primary particle exposed to the surface of the secondary particle.

11. The rechargeable lithium battery according to claim 1, wherein... The weight of the boron coating is greater than the weight of the boron coating portion at the grain boundaries.

12. The rechargeable lithium battery according to claim 1, wherein... The weight of the boron coating is at least four times the weight of the boron coating portion at the grain boundaries.

13. The rechargeable lithium battery according to claim 1, wherein... Based on the total amount of the boron coating and the grain boundary boron coating portion, the amount of the boron coating is 70 wt% to 98 wt%, and the amount of the grain boundary boron coating portion is 2 wt% to 30 wt%.

14. The rechargeable lithium battery according to claim 1, wherein... In the positive electrode active material, the primary particles are plate-shaped, and at least a portion of the plate-shaped primary particles are arranged radially.

15. The rechargeable lithium battery according to claim 14, wherein... The average length of the long axis of the plate-shaped primary particles is 150 nm to 500 nm, the average thickness is 100 nm to 200 nm, and the ratio of the average thickness to the length of the average long axis is 1:2 to 1:

5.

16. The rechargeable lithium battery according to claim 1, wherein... In the positive electrode active material, the secondary particles include an inner portion and an outer portion surrounding the inner portion, the inner portion including an irregular porous structure, and the outer portion including a radially arranged structure.

17. The rechargeable lithium battery according to claim 1, wherein... In the positive electrode active material, the lithium-nickel composite oxide is represented by the following chemical formula 1: [Chemical Formula 1] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2-z X z , in, In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.7, and 0 ≤ z ≤ 0.1, M 1 and M 2 Each of them is independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, Zr or any combination thereof, and X is F, P, S or any combination thereof.

Citation Information

Patent Citations

  • Cathode active material for secondary battery, manufacturing method therefor, and secondary battery including same

    CN108028369A

  • Lithium ion secondary battery

    CN108172772A

  • Cathode active material for lithium secondary battery, method for manufacturing same, and lithium secondary battery comprising same

    WO2021006520A1